Waktu Optimal Pelaksanaan Open Reduction and Internal Fixation pada Fraktur Maksilofasial - Adji, Iwan Setiawan; Arifinnia, Salwa Ghaisani Syariifah; Rosyita, Fadhilla Jihan; Hanief, Sekar Mayang Raisa; Nabilah, Aisyah; Alghozi, Muhammad Hilmi (FORIKES, 2025)
Maxillofacial fractures are complex injuries with serious functional and aesthetic implications. Determining the optimal timing of Open Reduction and Internal Fixation (ORIF) remains a matter of debate due to differences in clinical outcomes between early and delayed surgery. This issue is crucial to prevent complications such as infection, malunion, and occlusion disorders. The aim of this study was to systematically review the current scientific evidence regarding the effect of ORIF timing on clinical outcomes and complications in maxillofacial fractures. This study is a systematic literature review using the PRISMA 2020 guidelines. PubMed, ScienceDirect, and Google Scholar databases were searched for articles from 2008–2024 using the keywords “maxillofacial fracture,” “ORIF timing,” and “outcomes.” Ten studies met the inclusion criteria and were analyzed narratively based on parameters such as operative time, functional outcomes, and complications. Based on the study results, most studies indicate that early ORIF (≤72 hours) results in better bone healing (p <0.05), reduces the risk of infection and occlusion disorders, and accelerates masticatory rehabilitation. However, some studies report that delayed surgery up to 5–7 days can still provide comparable results if the soft tissue condition is unstable. The conclusion of this study is that current evidence supports the implementation of early ORIF if the patient's systemic condition permits. Delayed surgery should only be considered in cases with severe edema or high anesthetic risk.Keywords: maxillofacial fracture; open reduction and internal fixation; operative time; healing; complications ABSTRAK Fraktur maksilofasial merupakan cedera kompleks dengan implikasi fungsional dan estetik yang serius. Penentuan waktu optimal tindakan Open Reduction and Internal Fixation (ORIF) masih menjadi perdebatan, karena perbedaan hasil klinis antara operasi dini dan tertunda. Isu ini penting untuk mencegah komplikasi seperti infeksi, malunion, dan gangguan oklusi. Tunjuan dari studi ini adalah meninjau secara sistematis bukti ilmiah terkini mengenai pengaruh waktu pelaksanaan ORIF terhadap hasil klinis dan komplikasi pada fraktur maksilofasial. Studi ini merupakan systematic literature review menggunakan panduan PRISMA 2020. Basis data PubMed, ScienceDirect, dan Google Scholar ditelusuri untuk artikel tahun 2008–2024 dengan kata kunci “maxillofacial fracture”, “ORIF timing”, dan “outcomes”. Sebanyak 10 studi memenuhi kriteria inklusi dan dianalisis secara naratif berdasarkan parameter waktu operasi, hasil fungsional, dan komplikasi. Berdasarkan hasil studi, sebagian besar penelitian menunjukkan bahwa ORIF dini (≤72 jam) menghasilkan penyembuhan tulang yang lebih baik (p <0,05), menurunkan risiko infeksi dan gangguan oklusi, serta mempercepat rehabilitasi fungsi mastikasi. Namun, beberapa studi melaporkan bahwa operasi tertunda hingga 5–7 hari masih dapat memberikan hasil sebanding bila kondisi jaringan lunak belum stabil. Kesimpulan studi ini menyatakan bahwa bukti terkini mendukung pelaksanaan ORIF dini bila kondisi sistemik pasien memungkinkan. Penundaan operasi sebaiknya hanya dipertimbangkan pada kasus dengan edema berat atau risiko anestesi tinggi.Kata kunci: fraktur maksilofasial; open reduction and internal fixation; waktu operasi; penyembuhan; komplikasi